P53 expression in various types of hydropic placentas (through ploidy analysis as a complementary tool in diagnosis of samples) - Alireza Khooei; Fatemeh Atabaki Pasdar; Alireza Fazel; Mahmoud Mahmoudi; Mohammad Reza Nikravesh; shahrzad Daneshmand Shahbazian (Babol University of Medical Sciences, 2019)
Background: Placentas characterized by hydropic swelling of chorionic villi occur in a spectrum of pathological conditions including hydropic abortion (HA), partial hydatidiform mole (PHM) and complete hydatidiform mole (CHM). The purpose of this study was to investigate whether the expression of p53 tumour suppressor protein could differentiate these various types of hydropic placentas. Methods: p53 immunohistochemical staining was performed in 19 molar (8 PHM and 11 CHM) and 10 non-molar (HA) formalin-fixed, paraffin-embedded tissue samples. Ploidy analysis using flow cytometry was performed as a complementary tool in diagnosis of samples. Results: DNA histograms obtained from all samples had confirmed diploidy in HAs and CHMs and triploidy in PHMs. p53 immunoreactivity was assessed in villous cytotrophoblasts, syncytiotrophoblasts and stromal cells. The p53 positive reaction was predominantly observed in the nuclei of cytotrophoblastic cells and rarely in stromal cells, no reaction was seen in syncytiotrophoblasts. The mean percentage of p53 positive cells were 6.10±3.75 for HA, 25.87±13.4 for PHM and 39.83±18.76 for CHM.  There was a significant difference in P53 immunoreactivity of cytotrophoblastic cells between CHM and HA (P<0.001), and between PHM and HA (P=0.004). There was no significant difference in immunohistochemical reactivity between CHM and PHM (P=0.068). Conclusion: This study confirms that p53 immunostaining may be helpful in distinguishing complete and partial hydatidiform mole from hydropic abortion, but not complete hydatidiform mole from partial hydatidiform mole.